Ultra-high-performance liquid chromatography using a fused-core particle column for fast analysis of propolis phenolic compounds - Contieri, Letícia S.; de Souza Mesquita, Leonardo M; Sanches, Vitor L.; Viganó, Juliane; Kamikawachi, Renan Canute [UNESP]; Vilegas, Wagner [UNESP]; Rostagno, Mauricio A. (Wiley, 2023)
Propolis is a bee product with a complex chemicalcomposition formed by several species from different geographical origins. The complex propolis composition requires an accurate and reproducible characterization of samples to standardize the quality of the material sold to consumers. This work developed an ultra-high-performance liquid chromatography with a photodiode array detector method to analyze propolis phenolic compounds based on the two key propolis biomarkers, Artepillin C and p-Coumaric acid. This choice was made due to the complexity of the sample with the presence of several compounds. The optimized method was hyphenated with mass spectrometry detection allowing the detection of 23 different compounds. A step-by-step strategy was used to optimize temperature, flow rate, mobile phase composition, and re-equilibration time. Reverse-phase separation was achieved with a C18 fused-core column packed with the commercially available smallest particles (1.3 nm). Using a fused-core column with ultra-high-performance liquid chromatography allows highly efficient, sensitive, accurate, and reproducible determination of compounds extracted from propolis with an outstanding sample throughput and resolution. Optimized conditions permitted the separation of the compounds in 5.50 min with a total analysis time (sample-to-sample) of 6.50 min.
Keywords: Artepillin C; fast analysis; fused-core; p- Coumaric acid; propolis